Typological characterization of beekeepers in Campeche state, Mexico - Serralta-Batun, Laura-Patricia; Alamilla-Magaña, Juan-Carlos; Ramírez-Benítez, José-Efraín; Zarazúa-Escobar, José-Alberto; Monsalvo-Espinosa, José-Avelardo; Caamal-Velazquez, José-Humberto (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Beekeeping is a livestock activity that brings multiple benefits to humanity, in addition to its cultural value; therefore, it requires focused intervention within the framework of rural extension projects to optimize economic resources and capacities. Objective: To characterize the typology of the beekeepers that make up the honey production chain in the municipalities of Campeche, Calkiní, and Hopelchén in the State of Campeche. Methods: Surveys were applied to 220 beneficiary producers, stratified in terms of subsistence without market linkage (E1) and subsistence with market access (E2). Twenty social, economic, and technological variables were studied by main component and cluster analyses. Results: Five variables explain 65.81% of the variance: schooling, production experience, number of hives, yield/hive, and production per year. Four beekeeper profiles were identified. Type I includes beekeepers with 10 years of experience, production of 107.80 kg per year, and yield of 6.7 kg. Type II beekeepers have higher technological index, ten more years of productive experience, and completed basic education. Type III includes young beekeepers with completed high school and with the highest production of honey and yield and the same technological index as Type II. Type IV, elderly beekeepers with work logic more linked to the social and solidarity economy, all speaker of Mayan language with traditional organization schemes that obtain better yields per hive and honey production than Type I and II. Conclusions: This proposal can be used to typify producers from other regions in the context of Rural Extension Programs with a focused and differentiated vision in which development routes are required. Type III beekeepers could be the focus of Rural Extension Projects.